A case of V180I genetic mutation Creutzfeldt Jakob disease (CJD) with delusional misidentification as an initial symptom. Issue 1 (31st December 2022) - Nagata, Tomoyuki; Shinagawa, Shunichiro; Kobayashi, Nobuyuki; Kondo, Kazuhiro; Shigeta, Masahiro
ABSTRACT: An 84-year-old woman who had been diagnosed as having dementia with Lewy body (DLB) upon initial examination exhibited cognitive impairments and person delusional misidentification (DMS): she transiently claimed that her spouse was a stranger. She was re-examined at the age of 89 years; her frequency of speech and activities of daily living had both decreased, leading to verbal communication difficulties complicated by sensory aphasia, and brain diffusion-weighted (DW) magnetic resonance imaging (MRI) showed cortical hyperintensities in some areas of both hemispheres. About 4 months later, the DW high-intensity areas were observed to have expanded into diffuse cortical areas. While the clinical features of Creutzfeldt Jakob disease (CJD) (myoclonus; ataxia; parkinsonism; rapidly progressive cognitive impairments; periodic sharp discharges on electroencephalograms) were not observed, a genetic analysis of the prion protein ( PRNP ) gene, which was performed because of a family history of dementia, revealed a V180I mutation (heterozygosis: valine/isoleucine) suggesting genetic CJD (g-CJD). Her activity progressively decreased, reaching akinetic mutism about 11 months after the re-examination. Finally, she suffered from severe bedsores and died from aspiration pneumonia at the age of 90 years. The present report describes the first case of person DMS as an initial neuropsychiatric symptom for V180I g-CJD; the typical long-term clinical symptoms of CJD were not observed in this patient. The inclusion of person DMS as an initial clinical symptom and the presence of expansive cortical hyperintensity areas may be useful for clinicians attempting to diagnosis V180I g-CJD in patients with elusive symptoms.